Private extension system: An analysis - Lovleesh Garg,; T. S. Riar,; Manjinder Singh, (Journal of Agricultural Extension Management, 2025)
Under the liberalized economy, farmers have to modify and change their attitude and practices to cope with the new environment created by The World Trade Organization. They have to adopt the strategy of diversification and combination of different agricultural enterprises to compete in the world market. Moreover, when agriculture grows and becomes highly commercialized, farmers would require specialized information. There is a need for quick, accurate, timely and specific information for the success of specialized farming. Specialized and quality production needs heavy investment, thus, enhancing the risk. Therefore, farmers' requirement for agricultural information changes qualitatively. Presently almost all the extension services are provided by public sector except for a few attempts by private companies and NGO's. It has been seen 'that public sector extension services are not fully equipped to meet the new challenges. This is due to the non-availability of specialists with various state departments